2018
DOI: 10.1038/s41698-018-0053-2
|View full text |Cite
|
Sign up to set email alerts
|

SDH-deficient renal cell carcinoma associated with biallelic mutation in succinate dehydrogenase A: comprehensive genetic profiling and its relation to therapy response

Abstract: Succinate dehydrogenase (SDH)-deficient renal cell carcinoma (RCC) is a rare RCC subtype that is caused by biallelic mutation of one of the four subunits of the SDH complex (SDHA, B, C, and D) and results in inactivation of the SDH enzyme. Here we describe a case of genetically characterized SDH-deficient RCC caused by biallelic (germline plus somatic) SDHA mutations. SDHA pathogenic variants were detected using comprehensive genomic profiling and SDH absence was subsequently confirmed by immunohistochemistry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 27 publications
4
42
2
Order By: Relevance
“…Most reported cases with the classic morphology of SDH‐deficient RCCs have been associated with germline mutations in SDHB and SDHC . To date, only four cases have been reported to be associated with SDHA mutation, which, in addition to the loss of SDHB on immunohistochemistry, showed also a loss of SDHA . On the basis of the limited experience from these cases, SDHA‐deficient RCCs show higher nuclear grades, and a combination of variable morphologies that are different from that of typical SDH‐deficient RCC, including papillary, solid, cribriform and desmoplastic morphologies …”
Section: Sdh‐deficient Rccmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reported cases with the classic morphology of SDH‐deficient RCCs have been associated with germline mutations in SDHB and SDHC . To date, only four cases have been reported to be associated with SDHA mutation, which, in addition to the loss of SDHB on immunohistochemistry, showed also a loss of SDHA . On the basis of the limited experience from these cases, SDHA‐deficient RCCs show higher nuclear grades, and a combination of variable morphologies that are different from that of typical SDH‐deficient RCC, including papillary, solid, cribriform and desmoplastic morphologies …”
Section: Sdh‐deficient Rccmentioning
confidence: 99%
“…6 To date, only four cases have been reported to be associated with SDHA mutation, which, in addition to the loss of SDHB on immunohistochemistry, showed also a loss of SDHA. [9][10][11]26 On the basis of the limited experience from these cases, SDHA-deficient RCCs show higher nuclear grades, and a combination of variable morphologies that are different from that of typical SDHdeficient RCC, including papillary, solid, cribriform and desmoplastic morphologies. [9][10][11]26 The differential diagnosis of SDH-deficient RCC includes primarily oncocytoma and chromophobe RCC.…”
Section: Sdh-deficient Rccmentioning
confidence: 99%
“…SDH‐deficient renal carcinomas were first identified in 2004 (Vanharanta, et al, ) and accepted as a unique subtype of renal tumor in 2016 (Moch, Cubilla, Humphrey, Reuter, & Ulbright, ). Two recent studies have identified the variant SDHA p.Arg31stop, previously defined as the most prevalent mutation observed in SDH‐deficient (GISTs) (Miettinen & Lasota, ), in renal cancer patients (Carlo, et al, ; McEvoy, et al, ). Association of SDHx germline variants with thyroid cancer risk has also been described (Neumann, et al, ; Ni, et al, ), of particular relevance to the proband in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Comprehensive reviews of SDHA variants over a large disease spectrum in various databases have been published (Bannon, et al, ; Casey, et al, ; Evenepoel, et al, ). To date, there have been few reports of SDHA mutations in sporadic renal cancer: for example, a 17 kbp homozygous deletion leading to the loss of 9 exons of SDHA (Yakirevich, et al, ), a heterozygous germline mutation in the initiation codon (Jiang, et al, ), a splice site deletion (Ozluk, et al, ), and a combined germline/somatic biallelic loss (McEvoy, et al, ). The SDHA Ala45Thr variant was previously reported in a case of thoracic paraganglioma (Casey, et al, ) but was largely uncharacterized.…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic tumours can also arise because of somatic SDH mutations, as in the example of SDH‐deficient GISTs . The combination of a germline mutation with a ‘second‐hit’ somatic mutation seems to be the molecular background of the majority of SDH‐deficient renal cell carcinomas . Carney triad tumours are characterised by functional SDH deficiency, without SDH gene mutation .…”
Section: Introductionmentioning
confidence: 99%